SIKAP BAHASA SISWA SMPN 2 SIMANINDO DI SIMARMATA KECAMATAN SIMANINDO KABUPATEN SAMOSIR TERHADAP BAHASA INDONESIA - Afrita Sidabariba (Asas: Jurnal Sastra, 2013)
The purpose of this study was to determine the attitude of thelanguage students in SMP 2 Simanindo Simarmata, DistrictSimanindo Samosir regency on the Indonesian language. datasources in this research is the student SMP 2 Simanindo inSimarmata District Simanindo Samosir regency, amounting to 60students. Student attitudes SMP 2 Simanindo District Simanindo,Samosir regency positive for the Indonesian language. It is obviousfrom the results of the answers they give to questions / statements inthe questionnaire were distributed by the researchers followingresults 37 questions / statements (92.5%) showed a positive attitudetowards Indonesian. Only 3 questions / statements (7.5%), whichleads to negative attitudes towards the Indonesian language. Theresults also clarify the factors that influence students' attitudestowards SMP 2 Simanindo Indonesian. These factors are: (1)Background socio-economic status, education and employment, (2)emigration and (3) ethnic identityKeywords: Attitudes language students